Asesmen dalam Pendidikan: Konsep, Pendekatan, Prinsip, Jenis, dan Fungsi - Grisma Yuli Arta (Pusat Riset dan Inovasi Nasional, 2024)
Assessment is an integral component of learning in schools, playing a crucial role in measuring student achievement and enhancing the overall educational process. This article discusses challenges and strategies to improve teachers' understanding and skills in effective assessment implementation. Key challenges include the availability of adequate resources, teachers' readiness to use various assessment types, and societal expectations regarding evaluation standards.The research aims to explore how educators can enhance their assessment practices through continuous professional development. The research methodology employed includes literature review to identify best practices in assessment approaches, along with case analysis to understand implementations across different school contexts.The conclusion highlights the importance of enhancing teachers' understanding and skills in assessment as key to improving student learning quality. Teachers proficient in using diverse assessment types, providing meaningful feedback, and making instructional decisions based on assessment data can help create an inclusive and supportive learning environment. Therefore, focused professional development in assessment is a critical strategy in preparing educators to address future challenges in an increasingly complex and diverse educational landscape.